Library and information skills of newly enrolled diploma programme students in UiTM Kedah / Raja Alwi Raja Omar ...[et al.] - Raja Omar, Raja Alwi; Azmi, Nor Azlina; Md. Radzi, Mohd. Abdul Hafiz (2019)
Malaysia is heading towards becoming an information society and also a knowledge society (K-Society). On-going effort to establish our nation as center of academic excellence is seriously being taken and that includes reforming our educational system where part of it concerns with the inclusion of personal skills development. However one skill that many in the education fraternity fail to see or unwittingly neglect is the library and information skills among the school students. Through general observation (by librarians) on students enrolled into institutional of higher learning (public or private), it could be assume that majority of them do not possessed understanding and skills in information searching, or simply said, library or information illiterate. This could be seen in their inability to correctly use or find information resources relevant to their information needs. The researchers want to provide evidence and proof to reaffirm this inadequacy which may become a great obstacle in moving towards becoming an information society. A survey questionnaire and also a set of library skills assessment questions were distributed to new batch of students enrolled in the diploma program in UiTM Kedah. This batch of new students actually represents the Sijil Pelajaran Malaysia - SPM (and its equivalent) level of school leavers. They resemble characteristics of other SPM school leavers who managed to further their studies at other local or overseas universities and colleges, and also those who continued their daily life outside the academic world. The focus of assessment was on library skills (example, bibliographic instruction) because it was more fundamental and simpler than information skills. The outcome of the assessment will indicate whether we are truly lacking in the area of library skills provision to school students nationwide. If so, what should be the plan to eradicate the problem that has been too long in existences?